2022
DOI: 10.1212/wnl.0000000000012947
|View full text |Cite
|
Sign up to set email alerts
|

Hemiplegic Migraine Associated With PRRT2 Variations

Abstract: Background and objective:PRRT2 variants have been reported in a few cases of patients with hemiplegic migraine. To clarify the role of PRRT2 in familial hemiplegic migraine, we studied this gene in a large cohort of affected probands.Methods:PRRT2 was analyzed in 860 probands with hemiplegic migraine and PRRT2 mutations were identified in 30 probands. Genotyping of relatives identified a total of 49 persons with mutations whose clinical manifestations were detailed.Results:PRRT2 mutations were found in 12 of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Nevertheless, while accounting for some HM cases, particularly familial cases with severe phenotypes, we and others have found that <20% of clinically diagnosed cases have pathogenic variants in the FHM genes ( Hiekkala et al, 2018 ; Maksemous et al, 2019 ). Mutations in other genes including PRRT2 , PKND , ATP1A3 , SLC1A3 , SLC2A1 , and SLC4A4 can cause disorders with overlapping symptoms and have been implicated in some cases that present with HM ( Sutherland et al, 2019 ; Riant et al, 2022 ). Nevertheless, despite additional targeted analysis of whole-exome sequencing (WES) data for likely pathogenic variants in these genes, the majority of suspected HM cases remain genetically unsolved ( Pelzer et al, 2018 ; Sutherland et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while accounting for some HM cases, particularly familial cases with severe phenotypes, we and others have found that <20% of clinically diagnosed cases have pathogenic variants in the FHM genes ( Hiekkala et al, 2018 ; Maksemous et al, 2019 ). Mutations in other genes including PRRT2 , PKND , ATP1A3 , SLC1A3 , SLC2A1 , and SLC4A4 can cause disorders with overlapping symptoms and have been implicated in some cases that present with HM ( Sutherland et al, 2019 ; Riant et al, 2022 ). Nevertheless, despite additional targeted analysis of whole-exome sequencing (WES) data for likely pathogenic variants in these genes, the majority of suspected HM cases remain genetically unsolved ( Pelzer et al, 2018 ; Sutherland et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of ion‐regulating genes have been implicated in FHM, which is a rare monogenic form of migraine with aura that also includes motor disturbances and hemiparalysis (Goadsby et al., 2017 ). These include CACNA1A , ATP1A2 , SCN1A , and PRRT2 (De Fusco et al., 2003 ; Dichgans et al., 2005 ; Ophoff et al., 1996 ; Pelzer et al., 2014 ; Riant et al., 2012, 2022 ). Variants which have been implicated in FHM differ in their predicted effects, with ATP1A2 and PRRT2 having loss‐of‐function (LOF) variants, CACNA1A having gain‐of‐function variants, and SCN1A variants having a complex impact on protein function (Pietrobon & Moskowitz, 2013 ; Sutherland et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 ). The PRRT2 gene should be added to the main FHM genes because recent data have shown that PRRT2 is involved at least as frequently as SCN1A [ 29 , 30 ]. For convenience, we will therefore refer to FHM4 for HM associated with PRRT2 mutations.…”
Section: Familial Hemiplegic Migraine (Fhm) a Monogenic Form Of Migrainementioning
confidence: 99%